The role of organizational culture in the adoption of customer profitability analysis: a field study. Issue 1 (18th April 2017) - Fish, Matthew; Miller, William; Becker, D'Arcy; Pernsteiner, Aimee
Abstract : Purpose: The purpose of this paper is to examine the role of organizational culture as a company migrates through a four-stage model for designing a performance measurement system (PMS) focused on customer profitability. Design/methodology/approach: This is a single-site phenomenological case study, at Growth Spurt Marine Accessories (Growth Spurt), a manufacturing organization headquartered in the USA. Data were collected over a two-year period through interviews with accounting staff, internal company documents and recording observational notes. Findings: The paper identifies three major factors that prevented Growth Spurt from transitioning its customer profitability analysis (CPA) reporting package through Kaplan and Cooper's four-stage model of PMS design: executives exerting their power and spending political capital to prevent implementation without providing rationale, executives believing that the allocation methods were too subjective and executives relying on their own intuition in analyzing customer profitability rather than relying on data. These factors suggest that organizational culture plays an important role in migrating a customer-focused profitability PMS through Kaplan and Cooper's four-stage model of PMS system design. Research limitations/implications: The findings suggest that a PMS focused on customer profitability that does not advance beyond Stage II (financial reporting-driven) may still suit the needs of an organization. Additionally, managers should advocate for a multidisciplinary PMS design and implementation team to minimize potentially adverse effects of organizational culture. Originality/value: This paper is unique because it applies Kaplan and Cooper's four-stage model for PMS design to CPA and it uses a phenomenological case approach to explore impediments to a comprehensive CPA implementation.